2017
DOI: 10.5468/ogs.2017.60.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous cystadenocarcinoma of ovary with metastasis in 14-year-old girl

Abstract: Ovarian mucinous tumors in <15 years old are rare with <50 cases reported till date in the literature. Majority of them are benign or borderline epithelial ovarian tumors with only 12 cases of cystadenocarcinomas reported at a young age. We report a case of mucinous cystadenocarcinoma in 14-year-old girl with metastasis to omentum at the time of presentation. Management of such cases is tricky as conservative approach sparing fertility of the patient is adopted. This case is presented for its rarity and unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…It is this feature which makes them so dangerous; malignant ones are often inoperable by the time they are diagnosed, commonly in Stages III and IV. In our case patient presented with alarge right pelvic tumor associated with dull aching pain localized to the tumor 12 . The explanation of this is unknown; it can occur even before the growth erodes its capsule and is exposed to the peritoneum.…”
Section: Discussionmentioning
confidence: 71%
“…It is this feature which makes them so dangerous; malignant ones are often inoperable by the time they are diagnosed, commonly in Stages III and IV. In our case patient presented with alarge right pelvic tumor associated with dull aching pain localized to the tumor 12 . The explanation of this is unknown; it can occur even before the growth erodes its capsule and is exposed to the peritoneum.…”
Section: Discussionmentioning
confidence: 71%
“…20 Gupta et al also reported a case of Stage III mucinous cystadenocarcinoma of ovary with omental metastasis in a post menarchal 14 year old girl in which they gave systemic chemotherapy with cisplatin and paclitaxel. 21 A study by Aggarwal et al 22 found that low malignant recurrences have been reported more than ten years after initial surgery even in adult patients. Hence, close follow up is important for young patients also to monitor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of epithelial ovarian tumors in children is low, accounting for less than 20% among ovarian tumor types [ 1 ]. In addition, the vast majority of ovarian tumors in children are benign [ 2 , 3 ], while malignant ovarian epithelial neoplasms are extremely rare.…”
Section: Introductionmentioning
confidence: 99%